Proposta de um método baseado na abordagem Well-to-Wheel para calcular e avaliar as emissões de poluentes atmosféricos e GEE durante o ciclo de vida dos combustíveis utilizados por locomotivas - Caliman, Rafaella Ribeiro (2018)
Railways have a considerable share in the Brazilian cargo transportation, and it is expected to increase over the coming years. However, the growth of rail operations leads to a higher consumption of fossil fuels derived from petroleum by locomotives and consequently increase the emission of air pollutants and GHG. Due to recent environmental concerns, a number of measures have been taken worldwide to reduce emissions from the transport sector, for example the use of alternative fuels such as natural gas and biofuels. Nevertheless, it must be assessed whether such fuels are actually effective in reducing emissions when considering their entire life cycle, from raw materials acquisitions for fuel production to their final use in locomotives engines. Therefore, a method is proposed to calculate and evaluate air pollutants and GHG emissions during the life cycle of locomotives fuels, using as reference the international standard ISO 14040. This method was based on a Wellto-Wheel approach, usually applied to assess transportation fuels life cycles. It was applied to the Brazilian railway Estrada de Ferro Vitória a Minas for validation. Five scenarios were tested using the fuels B5, B25 and LNG. The results showed that the use of LNG associated to B25 by the locomotives would reduce CO2, CO, NOx and PM emissions in 33%, 19%, 59% and 83% respectively when comparing with the use of B5. The method also showed the importance of assessing the fuel life cycle emissions instead of locomotives engines emissions only, and can be use as a tool to support companies and regulatory agencies in the decision-making process.